PENGARUH PENDEKATAN KONTEKSTUAL BERBASIS BUDAYA LOKAL DAN KEMANDIRIAN BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Muhammad Khuluqin Hasan; Yuyu Yuhana; Hepsi Nindiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is often perceived as a scourge for elementary school students due to its abstract nature. This study aims to bridge the gap between abstract mathematical concepts and students' real-world experiences by integrating local cultural wisdom through a contextual approach. Specifically, this research examines the effect of a local culture-based contextual approach and learning independence on the understanding of mathematical concepts among fourth-grade students. Using a quasi-experimental method with a 2x2 factorial design, this study involved 40 students at SDN Pagedangan Udik I, Tangerang. Data were analyzed using Two-Way ANOVA. The results showed that: (1) students taught with a local culture-based contextual approach had significantly better conceptual understanding than those taught with conventional methods; (2) learning independence significantly influenced learning outcomes; and (3) there was an interaction between the learning model and learning independence. These findings suggest that bringing local culture into the classroom not only makes mathematics more concrete but also accommodates students with varying levels of learning independence, turning mathematics into a more humanistic and meaningful subject.